Pescadoras tradicionais, técnicas em pesca, “entendem-se incluídas” pela política pública do ProEJA? - Oliveira, Rosangela Gonçalves de (2016)
This research is a study of National Integration of Professional Education Policy with the Basic Education in the young and adults learners field, which calls itself an inclusive group of female students who studied in 2013 the blended learning Fishing Technician Course of ProEJA Highschool. This program was one of Luis Inácio Lula da Silva (2003 – 2010) and DilmaRousseff’s (2010 – 2014) government programs. It was established a parameter within their own lives perceptions as well as their communities after they have finished their course. The analyses ponder the concepts of inclusiveness from the subject perceptions discussing with the policy proposal and its theory. The research’s problem is inside of the real complexity with the possible contradictions, whichoccurs along with the course with the perspective of inclusiveness for traditional, crafter and worker adults.The hypotheses is that besidesof the work structural crises, it is possible to notice that there is an affirmative inclusiveness policy in a historic situation. According to the female students’ perceptions there are social power mechanisms, such as, their participation policy in their community.The research is developed in a real historiccontext and it uses the interpretation paradigm as its methodology with an eye in the contradiction. The research contains: interviews with fisherwomen from the five regions of the country; the community photographs; data and analyses of theFishing Technician Coursedocuments. Thefollowing authorsarecited: MARX, ENGELS, CHEPTULIN, GRAMSCI and FREIRE.The theses is structured in four sections. Chapter 1, “Navegational Chart: Our Methods” it is about the way which the research was developed, showing who were interviewed, as well as a structure perspective of their communities and regions, discussing with their talks in their interviews, and/or with the photographs taken by the researcher. Chapter 2, “Embarcation: The Course” it is about the Fishing Technician Course: its structure, dimension and curricular proposal, which includes a critical analysis. Chapter 3, “Coordinates: Paths Taken” it is about the theory which describes this thesis which are: the Subject, Work, Culture and Science/Technology’s understanding. Chapter 4, it is about a discussion of some authors who say about the concept of inclusiveness and education in the ProEJAprogram among the interviews taken and the analyzed documents. The last chapter is about the perspectives and the thesis itself, which is showed in the conclusion. To sum up, the hypothesis is partial confirmed because of the fisherwomen’s understanding of the inclusiveness concept by their conclusion of theirFishing Technician Course according to the Documento Base. Therefore, it is showed the opposite, because the same Documento Base and the other documents analyzed have as a goal the integral human formation and according to fisherwomen’s “inclusiveness” conception it is partial.